2013
DOI: 10.1177/0004867413508452
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological predictors of psychosocial function in bipolar disorder: Is there evidence that social cognitive and emotion regulation abnormalities contribute?

Abstract: There are reasonable theoretical grounds, supported by indirect and preliminary evidence, to suggest that social cognition and emotion regulation may be important in the prediction of psychosocial outcome in BD. However, this proposition is limited by the paucity of empirical research directly examining this matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 172 publications
(208 reference statements)
3
25
0
Order By: Relevance
“…However, despite both being clearly associated, they constitute different constructs . Some studies found that neurocognition predicts a significant percentage of the variance of social cognition in a way which could explain abnormalities in social cognition . In line with this, we observed that in a sample of euthymic patients with BD, alterations in emotion processing were present in a subgroup of patients with neurocognitive impairment .…”
Section: Discussionsupporting
confidence: 86%
“…However, despite both being clearly associated, they constitute different constructs . Some studies found that neurocognition predicts a significant percentage of the variance of social cognition in a way which could explain abnormalities in social cognition . In line with this, we observed that in a sample of euthymic patients with BD, alterations in emotion processing were present in a subgroup of patients with neurocognitive impairment .…”
Section: Discussionsupporting
confidence: 86%
“…The success of SC may contribute to psychosocial functioning in BD, given the role of these processes in facilitating social interactions and modulating psychosocial wellness so as to promote personal understanding and growth . On the contrary, deficits in SC, including EI, might reduce the accuracy of inferences made by patients concerning emotional state in others and limit the capacity for making social hypotheses which, in turn, may lead to a wide range of maladaptive psychosocial behaviors . Therefore, improving social‐emotional cognitive skills in patients is desirable since it not only would enhance the management of potential stressful situations derived from social interaction which could trigger relapses, but it would also improve both psychosocial functioning and quality of life .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is very likely that social cognitive impairments are implicated in decreased social functioning in affective disorders, the direct connection between social cognition and psychosocial outcomes has rarely been tested (Van Rheenan et al, 2014). Nevertheless, it is clear that social functioning is seriously impaired in patients with MDD (Hirschfeld et al, 2000) and bipolar disorder (Miklowitz, 2011).…”
Section: Social Cognition Abnormalities Across Diagnosesmentioning
confidence: 99%